2002
DOI: 10.1093/humrep/17.3.809
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of intravenous immunoglobulin in the prevention of recurrent miscarriage: evidence for a therapeutic effect in women with secondary recurrent miscarriage

Abstract: IvIg may improve pregnancy outcome in patients with secondary RM. A new placebo-controlled trial focusing on this subgroup should be conducted to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
1
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 22 publications
2
133
1
8
Order By: Relevance
“…In another study, the prevalence of a 14 base pair insertion in exon 8 of the HLA-G gene was found to be increased significantly in secondary RM patients, compared with controls. These studies provide evidence that particular HLA polymorphisms characterize secondary RM [5][6][7].Huge heterogeneity between eight randomized placebocontrolled trials of IVIg to patients with RM has been observed, with live birth rates in placebo groups ranging from 29 to 79% [8][9][10][11][12][13][14][15]. The differences in live birth rates observed between these studies raises questions as to whether the patient categories are the same.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the prevalence of a 14 base pair insertion in exon 8 of the HLA-G gene was found to be increased significantly in secondary RM patients, compared with controls. These studies provide evidence that particular HLA polymorphisms characterize secondary RM [5][6][7].Huge heterogeneity between eight randomized placebocontrolled trials of IVIg to patients with RM has been observed, with live birth rates in placebo groups ranging from 29 to 79% [8][9][10][11][12][13][14][15]. The differences in live birth rates observed between these studies raises questions as to whether the patient categories are the same.…”
mentioning
confidence: 99%
“…Huge heterogeneity between eight randomized placebocontrolled trials of IVIg to patients with RM has been observed, with live birth rates in placebo groups ranging from 29 to 79% [8][9][10][11][12][13][14][15]. The differences in live birth rates observed between these studies raises questions as to whether the patient categories are the same.…”
mentioning
confidence: 99%
“…There were some observations to support the theory that immunological factors played a greater role in women with a series of miscarriages after a birth (secondary RM) than in women with RM who had never had a successful pregnancy (primary RM). The HLA-DR3 allele found to be associated with RM displayed a much stronger association to secondary than to primary RM [56], and some evidence from immunotherapy studies suggested that a possible therapeutic effect of intravenous immunoglobulin (IvIg) seemed to be restricted to women with secondary RM [57]. During pregnancy fetal cells entered the maternal circulation of the women with secondary RM [58] and in late pregnancy apoptotic syncytiotrophoblast debris is normally shed in large quantities (several grams per day) from the placenta [59].…”
Section: Discussionmentioning
confidence: 99%
“…SRM was hence preceded by a possible priming of the immune system of the mothers that may theoretically lead to harmful immunological reactions against the semi-allogeneic fetus. Many women with secondary RM had developed a harmful immunological reaction against male-specific antigens(HY-antigens) on the trophoblast, and that this results in a subsequent increased miscarriage rate of male conceptions [57]. HY-derived peptides may be presented to maternal immune cells by HLA-G molecules on the trophoblast [60].…”
Section: Discussionmentioning
confidence: 99%
“…Paternal mononuclear cell immunization has been proved not to be effective (Scott, 2003). It is believed that passive immunotherapy with intravenous immunoglobulin (IVIG) may offer benefit in idiopathic secondary (at least one prior ongoing pregnancy), but not idiopathic primary (no prior ongoing pregnancy) recurrent miscarriage (Christiansen et al, 2002). However, such conclusions must be taken with caution because of small heterogeneous sample size.…”
Section: Immunotherapymentioning
confidence: 99%